Uma proposta para o ensino e aprendizagem dos conceitos de área de círculo e perímetro de circunferência - Paulo, Gilberto Pereira (2012)
This research had the purpose of studying the teaching and learning processes of concepts of circumference perimeter and circle areas on Junior High School. To develop the investigations, we sought to answer the following question: a didactic sequence with activities enabling the student to compare circumference perimeter and circle areas with perimeter area of other figures would minimize difficulties in the comprehension and differentiation of these two mathematical objects? Researches grounded in the didactic situation theory, in the dialectic of tool-object and semiotic presentation records, as well as principles of didactic Engineering. Target-public of the study is composed by students oh 9th year of Junior High School. Its results indicated an advance in the comprehension of the meaning of area as greatness and differentiation between circumference and circle, as well as between area and perimeter